-6(x+1)-8=-4(x-3)

Simple and best practice solution for -6(x+1)-8=-4(x-3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(x+1)-8=-4(x-3) equation:


Simplifying
-6(x + 1) + -8 = -4(x + -3)

Reorder the terms:
-6(1 + x) + -8 = -4(x + -3)
(1 * -6 + x * -6) + -8 = -4(x + -3)
(-6 + -6x) + -8 = -4(x + -3)

Reorder the terms:
-6 + -8 + -6x = -4(x + -3)

Combine like terms: -6 + -8 = -14
-14 + -6x = -4(x + -3)

Reorder the terms:
-14 + -6x = -4(-3 + x)
-14 + -6x = (-3 * -4 + x * -4)
-14 + -6x = (12 + -4x)

Solving
-14 + -6x = 12 + -4x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '4x' to each side of the equation.
-14 + -6x + 4x = 12 + -4x + 4x

Combine like terms: -6x + 4x = -2x
-14 + -2x = 12 + -4x + 4x

Combine like terms: -4x + 4x = 0
-14 + -2x = 12 + 0
-14 + -2x = 12

Add '14' to each side of the equation.
-14 + 14 + -2x = 12 + 14

Combine like terms: -14 + 14 = 0
0 + -2x = 12 + 14
-2x = 12 + 14

Combine like terms: 12 + 14 = 26
-2x = 26

Divide each side by '-2'.
x = -13

Simplifying
x = -13

See similar equations:

| 2(2x-2.2)=9x-4.4 | | -0.2x+2.91=-0.4x+1.11 | | -5w-(7/3)=(1/3w)-(3/4) | | 4x(x)+25x=0 | | (3/5u)-(4/3)=(-6/5u)=3 | | x^4+sqrt(17)*x^2-17=0 | | 7x-6=8x-9 | | 25/36-2/5(-1/3) | | 5(x+1.01)=4x | | (x+y)dx+(x+y)dy=0 | | -1/2x^2-7/2x-5 | | 1/2x^2-7/2x-50 | | (1/3w)-(4/3)=(-7/4w)-1 | | 5/6^2-2/5(-1/3) | | -1/2x^2-7/2x-50 | | 200x-0.05=600x+0.59 | | (-3/4v)-(3/4)=2v-(1/3) | | 3.1x-91=1.2x+4 | | (1/2)-(1/5y)=(-1/3) | | 6.1=10x+1.3 | | (3/4y)-(3/2)=(-2/3) | | Y-5.1=4 | | 0.9(3x+9)=5.2-(x-3) | | d/dx=[3*x/x^(3/2)] | | -2(p+7)-9=5p+12 | | 3*x/x^(3/2) | | 6(4x-8)-4=6(x-4)+98 | | 30x-6=60 | | 3-5y=5-6y | | 37-(2x+4)=2(x+4)+x | | 12x-y-840=0 | | x^2*x^9*x^8= |

Equations solver categories